2016
DOI: 10.1186/s40709-016-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Addressing huge spatial heterogeneity induced by virus infections in lentil breeding trials

Abstract: BackgroundSpatial heterogeneity can have serious effects on the precision of field experimentation in plant breeding. In the present study the capacity of the honeycomb design (HD) to sample huge spatial heterogeneity was appraised. For this purpose, four trials were conducted each comprising a lentil landrace being screened for response to viruses.ResultsHuge spatial heterogeneity was reflected by the abnormally high values for coefficient of variation (CV) of single-plant yields, ranging 123–162 %. At a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Lentil's transparent and thin seed coat is controlled by a recessive gene (tan) which moderates the tannin precursors that are responsible for seed darkening during cooking and the preservation period [9]. It is worth noting that both findings of our research group [10][11][12][13] and those of other research teams (for a review see Polidoros et al [1]) indicate that the genetic diversity present within and among lentil populations is rich enough to provide material for genetic studies and manipulation of this trait. Phenolic acids, stilbenes and flavonoids such as flavanones, flavones, dihydroflavonols, flavonols, flavan-3-ols, anthocyanidins and proanthocyanidins, also known as condensed tannins, are some of the derivatives of polyphenolic compounds that play an important role in the properties of the seed coat [14].…”
Section: Introductionmentioning
confidence: 70%
“…Lentil's transparent and thin seed coat is controlled by a recessive gene (tan) which moderates the tannin precursors that are responsible for seed darkening during cooking and the preservation period [9]. It is worth noting that both findings of our research group [10][11][12][13] and those of other research teams (for a review see Polidoros et al [1]) indicate that the genetic diversity present within and among lentil populations is rich enough to provide material for genetic studies and manipulation of this trait. Phenolic acids, stilbenes and flavonoids such as flavanones, flavones, dihydroflavonols, flavonols, flavan-3-ols, anthocyanidins and proanthocyanidins, also known as condensed tannins, are some of the derivatives of polyphenolic compounds that play an important role in the properties of the seed coat [14].…”
Section: Introductionmentioning
confidence: 70%
“…Fischer ( 2020 ) attributed the lack of widespread adoption to low heritability due to error variance and a larger area of land needed. On the other hand, Tokatlidis ( 2016 ) and Kargiotidou et al ( 2016 ) indicated that breeders do not need to be concerned with the soil heterogeneity that might induce the extra surface required, owing to the even and systematic entry allocation of the honeycomb designs. Discouraging results came from the mass selection at nil-competition in the rye plant (Pasini and Bos, 1990 ; Bussemakers and Bos, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…With interplant distance "d", the area occupied per plant is d 2 √ 3/2 [65]. Therefore, with single-plant hills spaced 1 m, the corresponding area per plant is 0.87 m 2 , and the area of the "109" circular control is about 95 m 2 , which is large enough to sample even huge levels of spatial heterogeneity [71]. Nevertheless, an even higher ring may be preferable in the case of a high ratio of missing plants in order to secure proper control for sampling the genetic heterogeneity.…”
Section: General Approach Of Breeding At Nil-competitionmentioning
confidence: 99%